Corrigendum: An audit of licenced radiological equipment and personnel in Botswana - Garebue D. Nlashwa; Morrison Sinvula; Setso O. Setso; Wallace Miller; Molatedi Lesiamang; Tashinga Maboreke; Richard D. Pitcher (Journal of the Colleges of Medicine of South Africa)
No abstract available.